A Lucid Lecturess: The Voices of New Zealand’s Silent Cinema - Hoar, P (My University, 2016)
This article attempts to record some of the faint echoes left from the days of silent cinema in New Zealand. Sound has been an integral part of cinematic experience in New Zealand since the very first exhibitions during 1895 but the acoustic dimension of film has been little explored by local historians and media scholars. Cinema audiences listened as much as they watched and these sounds were generated by many sources from gramophones to orchestras. This article concentrates on just one aspect of this richly polyphonic cinematic soundscape: the human voice. Through a discussion of the ways in which lecturers, actors, and audiences used their voices as films were played, this article recovers important aspects of how films were experienced in New Zealand before the arrival of synchronised sound and pictures during the late 1920s.
Keywords: Silent Cinema; Voice; Film History; Audiences; Listening